Meta-Analysis: The Effect of Breathing Exercise on Respiratory Function in COVID-19 Patients - Lilik Sigit Wibisono; Lily Nabillah (Masters Program in Public Health, 2021)
Background: COVID-19 is an infectious disease caused by a virus. Globally, in January 2022 the number of new cases of COVID-19 increased by 5%, which is more than 21 million new cases. Signs and symptoms commonly found in COVID-19 patients are acute respiratory disorders such as fever, cough, and shortness of breath. Breathing exercise in the form of a method of breathing in a certain way helps to improve and improve lung performance which is good for quality of life. This study aims to analyze the effect of breathing exercises on respiratory function in COVID-19 patients.Subjects and Method: A systematic review and meta-analysis was conducted by collecting articles from the Google Scholar, PubMed, and Science Direct databases. The articles were filtered using the PICO model, including: Population= confirmed COVID-19 patients. Intervention= breathing exercises. Comparison= conventional breathing exercises. Outcome= respiratory func